2017
DOI: 10.1097/won.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Chinese Persons Living With an Ostomy

Abstract: Health-related quality of life among Chinese patients with fecal ostomies was less than optimal and influenced by multiple demographic and psychosocial factors. Additional research is needed to design strategies to improve HRQOL in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 44 publications
5
53
1
5
Order By: Relevance
“…24 The quality of life of ostomate can be improved by identifying and addressing perceptions and mental health for appropriate education for mastery of colostomy care. 7,13 Our findings of higher level of symptoms of depression during early postoperative period of stoma after radical surgery for rectal cancer affirm the need of specialized care for these patients. The possible limitations of our study could be the single center with limited sample not fully representative of all colostomy patients.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…24 The quality of life of ostomate can be improved by identifying and addressing perceptions and mental health for appropriate education for mastery of colostomy care. 7,13 Our findings of higher level of symptoms of depression during early postoperative period of stoma after radical surgery for rectal cancer affirm the need of specialized care for these patients. The possible limitations of our study could be the single center with limited sample not fully representative of all colostomy patients.…”
Section: Resultsmentioning
confidence: 52%
“…6 Colostomy leads to anxiety and depression with less than optimal quality of life (QOL). 7 Zung SDS 8 is a reliable and valid tool, also used in Chinese population. [9][10][11][12] Identifying and addressing their perceptions and mental health status for appropriate education for mastery of colostomy improves the QOL.…”
Section: Introductionsmentioning
confidence: 99%
“…The quantitative study conducted by Genz et al, (2017) to 93 years old, consisting of both men and women. The setting was from rural hospitals settings in China.…”
Section: Chapter 2: Literature Reviewmentioning
confidence: 99%
“…The setting was from rural hospitals settings in China. The data was collected utilizing the administration of the City of Hope quality of life ostomy questionnaire in the Chinese version, stoma self-efficacy scale-Chinese version, Ostomy adjustment inventory-Chinese version, social support revalued scale and the hospital anxiety depression scale (HADS), also in the Chinese version (Genz et al, 2017). All the tools utilized were standardized tools validated in previous research studies and shown to be reliable and valid.…”
Section: Chapter 2: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation